2000
DOI: 10.1034/j.1600-0609.2000.90079.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in patients with malignant non‐Hodgkin's lymphoma

Abstract: Splenectomy in patients with non-Hodgkin's lymphoma (NHL) is performed for either diagnostic or therapeutic reasons. We report on a series of 29 patients with NHL and splenomegaly who underwent splenectomy during the years 1979-1998 in our hospital. According to the indication for splenectomy our patients were categorized in three groups. Group A: In 20 patients splenectomy was performed for diagnostic reasons. Group B: Three patients were splenectomized for autoimmune haemolytic anaemia (AIHA). Group C: Six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…1 Splenic volume changes after RIT were found in the NHL patients who had enlarged spleens, a condition wherein histologic NHL involvement is more likely. In 28 NHL patients who had a splenic mass greater than 500 g and who underwent splenectomy, Xiros et al 27 found that 27 patients (96%) had histologic NHL involvement of the spleen. In our study, 13 NHL patients with splenic volumes of 380-1400 mL had splenic volume decreases of 70-550 mL after being associated with a low radiation dose to the spleen ( Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…1 Splenic volume changes after RIT were found in the NHL patients who had enlarged spleens, a condition wherein histologic NHL involvement is more likely. In 28 NHL patients who had a splenic mass greater than 500 g and who underwent splenectomy, Xiros et al 27 found that 27 patients (96%) had histologic NHL involvement of the spleen. In our study, 13 NHL patients with splenic volumes of 380-1400 mL had splenic volume decreases of 70-550 mL after being associated with a low radiation dose to the spleen ( Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Xiros et al maintain that the median survival after diagnostic splenectomy is 24 months regardless of disease stage or adjuvant chemotherapeutic regimen. 11 Treatment for PSL sparks debate due to the lack of clinical trials. Possible treatment modalities include splenectomy, local radiotherapy and systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with malignant hematologic diseases have a high surgical risk, with morbidities after the splenectomy ranging from 3.5% to 61%. [13][14][15] The most common and serious complications include disseminated intravascular coagulation, portal vein thrombosis, pulmonary embolism, atelectasis, pleural effusion, subphrenic abscess, and postoperative hemorrhage. [16][17][18] A splenic weight greater than 3000 g poses an especially high risk for portal vein thrombosis, with an incidence of 50%.…”
Section: Discussionmentioning
confidence: 99%